Strength training : Methods, health benefits & doping (Physical Fitness, Diet and Exercise, 2016)
Before thinking about which exercises, frequency and intensity should be used in strength training programs to achieve muscle strength, promote a healthy lifestyle, hypertrophy or improve athletic performance, we should understand firstly how a muscle contraction happens. The aim of this book is to provide you with a basic to advanced understanding about several physiological systems involved in muscle contraction: physiological adaptations for exercises, especially strength exercises; molecular responses; methods of training; nutrition and muscle performance; muscle recovery; benefits of strength exercises to human health; and which drugs are commonly used for doping in different sports. Chapter One of this book will review all of the most important cells, structures and processes involved in muscle contraction, such as neurons cells, synapses, motor units, general and molecular mechanisms of muscle contraction. Chapter Two will describe the most important bioenergetics pathways of energy supplies required for muscle contraction. After understanding how muscle contraction happens and how energy is supplied, the reader will discover principles, methods and physiological adaptations of skeletal muscles to strength trainings within Chapters Three, Four and Five. In particular, Chapter Four will provide a friendly and detailed account of molecular adaptation in skeletal muscles to different exercises, discussing differential gene expression and the effects of different exercises in different populations and disorders. This book also points out a very important and detailed factor concerning cryotherapy in Chapter Six, one of most common strategies used to promote muscle recovery. Specific orientations regarding nutrition and muscle performance are presented in Chapter Seven, while doping and different drugs used to increase muscle performance in several sports introduce Chapter Eight. Finally, Chapter Nine describes the benefits of strength training to diabetic, hypertensive, obese and myopathic patients. We strongly believe that all kwledge within this book is essential for all professionals working to promote the health of patients and increase physical performance of athletes or their clients, as well as for all people linked to sports and physical activity in some way.